2001
DOI: 10.1046/j.1354-1013.2001.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene emission and monoterpene synthase activities in the Mediterranean evergreen oak Quercus ilex L. grown at elevated CO2 concentrations

Abstract: Monoterpene emissions, monoterpene synthase activities, photosynthesis, fluorescence yield in the dark and drought stress indicators (stomatal conductance and mid‐day water potential) were concurrently measured under similar temperature and illumination in current‐year leaves of Quercus ilex L. of plants grown in open‐top chambers at ambient (350 ppm) and elevated (700 ppm) CO2. The study was undertaken to understand the effect of CO2 on monoterpene biosynthesis, and to predict and parameterize the biogenic em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
102
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 28 publications
10
102
2
1
Order By: Relevance
“…The higher terpene emission rates in summer than in spring were also explained mostly by a large change in emission factor (capacity). Q. ilex is a strong emitter of terpenes, especially in warm summer conditions (Staudt and Seufert, 1995;Kesselmeier et al, 1996;Street et al, 1997;Holzinger et al, 2000;Llusia and Peñuelas, 2000;Loreto et al, 2001;Owen et al, 2001;Staudt et al, 2002;Plaza et al, 2005;Llusia et al, 2011). The Q. ilex monoterpene emission rates were 6.4 (3.7 for standardised values) times higher in summer than in spring, similar to reports of Llusia et al (2011) in a atypically warm and dry summer.…”
supporting
confidence: 67%
“…The higher terpene emission rates in summer than in spring were also explained mostly by a large change in emission factor (capacity). Q. ilex is a strong emitter of terpenes, especially in warm summer conditions (Staudt and Seufert, 1995;Kesselmeier et al, 1996;Street et al, 1997;Holzinger et al, 2000;Llusia and Peñuelas, 2000;Loreto et al, 2001;Owen et al, 2001;Staudt et al, 2002;Plaza et al, 2005;Llusia et al, 2011). The Q. ilex monoterpene emission rates were 6.4 (3.7 for standardised values) times higher in summer than in spring, similar to reports of Llusia et al (2011) in a atypically warm and dry summer.…”
supporting
confidence: 67%
“…It would seem that algorithms that include solely a response to increasing temperature would be more sensitive under future warming scenarios compared to those that also include a light-limitation, but the overall effects of climate change on other important processes like changes in leaf area index or vegetation cover would also need to be considered. What is more, it is uncertain whether the response of monoterpene production to increasing atmospheric CO 2 concentration follows a similar inhibitory pattern as is shown for isoprene in an increasing number of plants (Constable et al, 1999;Loreto et al, 2001;Staudt et al, 2001;Baraldi et al, 2004), although the similarity in the chloroplastic pathways would suggest a similar response.…”
Section: Discussionmentioning
confidence: 93%
“…Isoprene is formed predominantly from photosynthetic carbon fixation (Sharkey & Yeh 2001) and it was expected that the two processes be simultaneously stimulated by increasing availability of CO2. However, exposure to or growth at elevated CO2 often reduce isoprenoid emission by vegetation (Loreto & Sharkey 1990, Loreto et al 2001a, Scholefield et al 2004, Rosen stiel et al 2003, with few exceptions (e.g., Sharkey et al 1991, Rapparini et al 2001. This uncoupling between the two processes may be due to an inhibition of isoprene syn thase activity under elevated CO2 (Schole field et al 2004) or to a reduction of the availability of isoprene synthase substrate (predominantly dimethylallyl diphosphate (DMADP), Rosenstiel et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike photosynthesis, phytogenic iso prenoid emissions are relatively insensitive to, or are even negatively affected by elevat ed CO2 (Sharkey & Yeh 2001, Loreto et al 2001a. Sharkey et al (1991) found that the basal emission in Populus tremuloides seedlings grown in growth chambers was re duced by 30-40% in response to elevated CO2 (900 ppm).…”
Section: Introductionmentioning
confidence: 99%